PENGARUH LOYALITAS KERJA DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN KOPERASI SIMPAN PINJAM PARODANA “M” TAMBAK KABUPATEN SERANG - Gatot Hartoko; Kusmini Kusmini; Munawaroh Munawaroh (Universitas Bina Bangsa, 2022)
This study uses a quantitative approach using a survey method with a saturated sample where the population is all sampled, namely 50 respondents with primary and secondary data collection techniques. The results of the research variable work loyalty and teamwork have a significant effect simultaneously on employee performance. It is proven by the Sig value of 0.000 which is smaller than 0.5. The R value of 0.824 means that it is included in the very strong correlation interval. The results of the F test show the Fcount > Ftable (49.707 > 3.20) and the significance value < (0.000 < 0.05), then H0 is rejected and Ha is accepted. The value of the coefficient of determination seen from the RSquare is 0.679. It can be concluded that the contribution of work loyalty (X1) and teamwork (X2) to employee performance (Y) is 67.9%, while the remaining 32.1% is influenced by other variables not explained in this research model. There is a significant influence between work loyalty and teamwork on the performance of the employees of the Parodana Savings and Loans Cooperative